THE EFFECT OF EXCHANGE RATE AND INTEREST RATE ON SHARE PRICES IN THE MANUFACTURING SECTOR WITH INFLATION AS MODERATION - Sugiyanto Ikhsan; Toufiq Agung Pratomo Sugito Putra; Sugiyanto Sugiyanto; Rima Dasuki; Endra Herdiansyah (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2022)
The movement of stock prices during the COVID-19 pandemic crisis has shown significant changes, this can be seen from the decline in the Composite Stock Price Index (JCI). This condition encouraged research in the field of macroeconomics to be able to understand this phenomenon. This research aims at examining the effect of macroeconomics on stock prices by using the manufacturing sector as the object of research. This research used the 2020 period, where in that period the JCI fell. The results showed that only the exchange rate had an effect on stock prices in the manufacturing sector, while inflation and interest rates had no effect on stock prices in the manufacturing sector. Inflation which is used as a moderating variable can moderate the effect of exchange rates and interest rates on stock prices in the manufacturing sector.